Effectiveness of the ‘BANGKIT’ Program to Support the Implementation of ‘Merdeka’ Curriculum in Primary Schools in a Wetland Environment - Noorhapizah, Noorhapizah; Prihandoko, Yogi; Pratiwi, Diani Ayu; Saputra, M. Diki (Journal of Education Method and Learning Strategy, 2024)
This research is motivated by the flexibility provided by the independent curriculum to educational units to develop school programs that suit local geographic, social and cultural characteristics. Higher education institutions as school partners need to conduct research and develop school programs that are relevant to the wetland environment. This research aims to determine the level of effectiveness of the '‘BANGKIT’' school program which is an acronym for Moral, Religious, Numeracy & Literacy, Environmental Care Movement, Collaboration, Information & Technology which is a reference for developing elementary school level school programs in the wetland environment of South Kalimantan. This research used the Research and Development method, the research subjects were 191 elementary school students in South Kalimantan, Indonesia. The research results show that the '‘BANGKIT’' program has proven to be significantly effective in increasing students' moral, religious, numeracy, literacy, ecological, collaboration and technology mastery competencies in wetland environments. The results of this research are supported by the results of the mean difference test using the paired sample t-test method with the help of SPSS software which shows a significance value that is smaller than 0.05 (0.05>0.000), the t-test value is greater than the t-table (2.337> 0.67667), and the posttest mean score was higher than the pretest (137.15>135.05). The level of increase if calculated using the N-Gain method shows a result of 0.312, which means there is an increase in the moderate category.